2011
DOI: 10.1039/c1cc14347f
|View full text |Cite
|
Sign up to set email alerts
|

syn-Selective asymmetric cross-aldol reactions between aldehydes and glyoxylic acid derivatives catalyzed by an axially chiral amino sulfonamide

Abstract: syn-Selective asymmetric cross-aldol reactions of aldehydes with tert-butyl glyoxylate and glyoxamide were realized by the use of an axially chiral amino sulfonamide (S)-1. The cross-aldol products obtained are densely functionalized and readily converted to synthetically useful and important chiral building blocks such as γ-lactone and γ-lactam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…On the other hand, with the binaphthyl-based amino sulfonamide (S)-1 as catalyst, both tertbutyl glyoxylate and glyoxamide 13 were transformed to the corresponding syn-aldol adducts predominantly with excellent enantioselectivity (Scheme 2). 6 The observed switch in diastereoselectivity can be well explained by transition state models as shown in Fig. 4.…”
Section: Aldol Reactionmentioning
confidence: 77%
See 1 more Smart Citation
“…On the other hand, with the binaphthyl-based amino sulfonamide (S)-1 as catalyst, both tertbutyl glyoxylate and glyoxamide 13 were transformed to the corresponding syn-aldol adducts predominantly with excellent enantioselectivity (Scheme 2). 6 The observed switch in diastereoselectivity can be well explained by transition state models as shown in Fig. 4.…”
Section: Aldol Reactionmentioning
confidence: 77%
“…The obtained aldol adducts were versatile intermediates in organic synthesis and were readily converted to important chiral building blocks (Scheme 3). 6 The aldol adduct 12 (syn/anti ¼ 4.7/1) could be converted to g-lactam 15 (anti/syn ¼ 4.0/1) by reductive amination and heating of the resulting amine. When the aldol adduct 14 (syn/anti ¼ 17/1) was treated with 4 M HCl under reux, g-lactone 16 (anti/syn ¼ 17/1) was obtained in good yield with complete retention of the stereochemistry.…”
Section: Aldol Reactionmentioning
confidence: 99%
“…With both N -protected aldehydes 3c and 8b in hand, we next investigated their reductive amination to access pseudoenantiomeric lactamic cDAA precursors (Scheme ). The reaction of 3c with benzylamine using NaBH 3 CN or NaBH­(OAc) 3 in the presence of acetic acid, respectively, without or with preformation of the corresponding imine (Scheme , eq 1), afforded the corresponding secondary amine 9c in good yield (70%). When extended to ( R )-α-methylbenzylamine, the reductive amination was performed in 77% yield ( 10c ).…”
Section: Resultsmentioning
confidence: 99%
“…After evaluation of reaction conditions, we found that sterically bulky tert ‐butyl glyoxylate 21 is effective to improve the stereoselectivity. In the presence of 2 mol% of I , the reaction between propanal and tert ‐butyl glyoxylate 21 produced syn ‐aldol adducts 22 a in moderate yield with high selectivity in acetonitrile at room temperature for 1 hour (Scheme 13a, 61 % yield, syn / anti =5.3/1, 97 % ee) [21] . Under the identical reaction conditions, several aldehydes 1 were employed and the corresponding syn ‐aldol adducts 22 b ‐ e were afforded in high yield with moderate syn ‐selectivity, and excellent enantioselectivity.…”
Section: Axially Chiral Biaryl‐based Secondary‐amino Tf‐amide Catalysismentioning
confidence: 99%